The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007 IEEE Swarm Intelligence Symposium 2007
DOI: 10.1109/sis.2007.368045
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Swarm for the Quadratic Knapsack Problem

Abstract: Abstract-The 0-1 quadratic knapsack problem (QKP) is a hard computational problem, which is a generalization of the knapsack problem (KP). In this paper, a mini-Swarm system is presented. Each agent, realized with minor declarative knowledge and simple behavioral rules, searches on a structural landscape of the problem through the guided generate-and-test behavior under the law of socially biased individual learning, and cooperates with others by indirect interactions. The formal decomposition of behaviors all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The ABC [15] algorithm has been shown to outperform Mini-Swarm [14] both in terms of probability to reach the optimal and time taken to compute them. Mini-Swarm provides 7590 hits to optimal out of 8000 trials for 100 and 200 object instances while ABC hits optimal 7892 times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABC [15] algorithm has been shown to outperform Mini-Swarm [14] both in terms of probability to reach the optimal and time taken to compute them. Mini-Swarm provides 7590 hits to optimal out of 8000 trials for 100 and 200 object instances while ABC hits optimal 7892 times.…”
Section: Resultsmentioning
confidence: 99%
“…Julstrom [12] presented studies on various greedy and genetic algorithms and has shown a greedy genetic algorithm (GGA) to solve a sample of Billionet and Soutif's benchmark instances [13] (BS benchmark instances) with up to 200 variables to optimality in 902 out of 1000 trials using around 15000 Function Evaluations (FES) on an average per trial. A Mini-Swarm algorithm is proposed by Xie and Liu [14] and an artificial bee colony (ABC) algorithm by Pulikanti and Singh [15] which are shown to solve all BS benchmark instances with up to 200 binary variables to optimality with high probability (0.949 and 0.987 respectively) in a very reasonable time. The ABC algorithm has been shown to outperform Mini-Swarm in [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Mini-Swarm algorithm is proposed by Xie and Liu (2007) is shown to solve all BS benchmark instances with 100 and 200 binary variables to optimality with high probability in a reasonable time. Patvardhan et al (2012) presented known best QIEA for QKP (dubbed QIEA-PPA in this paper).…”
Section: The Quadratic Knapsack Problem (Qkp)mentioning
confidence: 99%
“…It is clear that QIEA-QKP outperforms both QIEA-PPA and GGA in terms of frequency of reaching optimal and computational effort required. Table 9 shows the comparison of proposed QIEA-QKP with the a popular population-based Mini-Swarm algorithm given by Xie and Liu (2007) using BS benchmark instances of size 100 and 200 variables. Table 9 presents number of times optimal solution is reached in 100 runs (Hits), average value over 100 runs of relative percentage deviation (RPD) from the optimal and average time taken (AvgT) in seconds required to reach best solution.…”
mentioning
confidence: 99%